Export promotion policies in Central America - Willmore, Larry (1997)
Notes that member countries of the Central American Common Market are now encouraging non-traditional exports by lowering tariff barriers, unifying exchange rates and giving exporters access to intermediate and capital goods at international prices. Reviews these policies and examines their effects on the exports of each of the five member countries, with special attention to the possiblity that the subbsidies granted in respect of goods exported outside the Central Ameical Common Market may induce exporters to switch from regional to extraregional markets.